Glider observations and modeling of sediment transport in Hurricane Sandy. Issue 3 (19th March 2015) - Miles, Travis; Seroka, Greg; Kohut, Josh; Schofield, Oscar; Glenn, Scott
Abstract Regional sediment resuspension and transport are examined as Hurricane Sandy made landfall on the Mid‐Atlantic Bight (MAB) in October 2012. A Teledyne‐Webb Slocum glider, equipped with a Nortek Aquadopp current profiler, was deployed on the continental shelf ahead of the storm, and is used to validate sediment transport routines coupled to the Regional Ocean Modeling System (ROMS). The glider was deployed on 25 October, 5 days before Sandy made landfall in southern New Jersey (NJ) and flew along the 40 m isobath south of the Hudson Shelf Valley. We used optical and acoustic backscatter to compare with two modeled size classes along the glider track, 0.1 and 0.4 mm sand, respectively. Observations and modeling revealed full water column resuspension for both size classes for over 24 h during peak waves and currents, with transport oriented along‐shelf toward the southwest. Regional model predictions showed over 3 cm of sediment eroded on the northern portion of the NJ shelf where waves and currents were the highest. As the storm passed and winds reversed from onshore to offshore on the southern portion of the domain waves and subsequently orbital velocities necessary for resuspension were reduced leading to over 3 cm of deposition across the entire shelf, just north of Delaware Bay. This study highlights the utility of gliders as a new asset in support of the development and verification of regional sediment resuspension and transport models, particularly during large tropical and extratropical cyclones when in situ data sets are not readily available.